(untitled) (Journal of Rangpur Medical College, 2025)
Background: Thalassemia is a prevalent genetic disorder in South Asia, including Bangladesh, where transfusion-dependent patients are at risk of iron overload. Deferasirox, an oral iron chelator, is widely used to manage iron burden. Objective: This study evaluates the efficacy of deferasirox in thalassemic children. Methods: This pretest-posttest quasi-experimental study was conducted at the Bangladesh Shishu (Children) Hospital and Institute, Dhaka, involving 50 transfusion-dependent thalassemic children aged 2–18 years. Serum ferritin was measured before and after six months of deferasirox therapy. Statistical analysis included paired t-tests, with p-values <0.05 considered significant. Results: The mean serum ferritin level decreased significantly from 2462±1169 ng/mL to 1874±1002 ng/mL (p<0.001), with a mean reduction of 588±367 ng/mL and a percentage reduction of 24.60±13.00%. Conclusion: Deferasirox effectively reduces serum ferritin levels in transfusion-dependent thalassemic children. These findings contribute to evidence-based strategies for managing iron overload in resource-limited settings. J Rang Med Col. March 2025; Vol.10, No.1: 82-86